Consumer Evaluations of Social Alliances: The Effects of Perceived Fit Between Companies and Non-Profit Organizations - Kim, Namin (Journal of business ethics, 2012)
Company–cause fit has been one of the major issues in the domain of corporate social responsibility. This study tries to expand the perspective from company–cause to company–non-profit organization (NPO) fit, and it gives implications to firms looking for long-term collaboration with an NPO. Specifically, it suggests three types of fit, i.e., familiarity, business, and activity fit and investigates the potential effects of these fits in social alliances between companies and the partnering NPOs on consumer attributions of the firms’ motives for the alliances. An experiment that used scenarios revealed that consumers perceive high-fitted alliances on the dimensions of the familiarity and activity fit as being more public-serving than low-matched ones. However, the consumers’ attribution of the motive is not different between the high and low business fit. The implications of the research results are discussed from an academic and practical standpoint.